Analysis of Buerger Allen Exercise Interventions in Improving Peripheral Perfusion in Nursing Care for Type 2 Diabetes Mellitus Clients in the Inpatient Room: Case Report: Analisis Intervensi Buerger Allen Exercise dalam Meningkatkan Perfusi Perifer Pada Asuhan Keperawatan Klien Diabetes Melitus Tipe 2 Di Ruang Rawat Inap: Laporan Kasus - Millenia, Nadia; Tutiany, Tutiany (Essential English Grammar, 2024)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. Most causes occur due to impaired insulin secretion, impaired insulin action,  impaired carbohydrate, fat, protein metabolism. The results of the Basic Health Research in 2018 showed that the prevalence of DM in Indonesia is 8.5% or around 20.4 million people diagnosed with diabetes mellitus. In Jakarta (Kemenkes RI, 2018). It is estimated that a person with diabetes has a 25% lifetime risk of developing diabetic ulcers (International Diabetes Federation, 2020). One of the common nursing problems in DM clients is ineffective peripheral perfusion. Buerger Allen Exercise is one of the active movement exercises that aims to improve peripheral perfusion to the lower extremities. This case report aims to analyze nursing care in the application of Buerger Allen Exercise interventions in clients with Diabetes Mellitus. The research method used is descriptive research in the form of a case study with a sample of 1 person conducted for 3 consecutive days with a duration of 12 minutes in the morning and evening in the internal medicine inpatient room. The results of the evaluation after the intervention of the Buerger Allen exercise found a change in ABI values on the first day of the right ABI value: was 0.87 and the left ABI: was 0.80, on the second day the right ABI value was 1.2 and the left ABI was 1.03, on the third day the right ABI value was 1.01 and the left ABI: 1,0. For CRT, pulse on the extremities, and edema there were no significant changes. While in the acral there is a change to warm acral on the lower extremities. This shows the effectiveness of the Buerger Allen exercise on lower extremity peripheral perfusion, especially in increasing ABI values